Optimizing Care Delivery by Applying an Innovative Shared Medical Appointment Model for Determination of Cochlear Implant Candidacy. Issue 8 (September 2021) - Sydlowski, Sarah; Donovan, Cara; McNair, Jordan; Hahn, Katie; Petter, Karen; Marks, Tina; Haberkamp, Tom; Nguyen-Huynh, Anh; Podriznik, James; Woodson, Erika
Abstract : Objective: To develop and implement an innovative group appointment with the potential to improve access to cochlear implantation (CI) while maintaining patient satisfaction and experience. Patients: Adult patients with advanced sensorineural hearing loss. Intervention(s): Implementation of novel shared medical appointment (SMA) model. Main Outcome Measure(s): Patient satisfaction with group visit; anecdotal description of provider efficiency and experience. Results: Survey data were collected from 166 adults who participated in a group CI candidacy appointment from September 2017 to February 2020 as part of a quality improvement initiative. Provider time is anecdotally optimized by accommodating more patients in a shorter timeframe while effectively triaging those candidates most likely to meet candidacy criteria for a full CI evaluation. Most importantly, patient feedback has been positive which suggests that patients find value in this novel format. Conclusions: The current climate of healthcare demands that providers maximize the efficacy and efficiency of patient care. Our large CI program has determined that using an SMA format as an entry point for CI candidacy evaluation offers many benefits. The group appointment improves patient throughput and also provides a positive patient experience. Group visits offer a viable solution for increasing patient access to CI while maintaining quality in a busy academic medical center setting.